2007
DOI: 10.1111/j.1600-0404.2007.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early interferon beta-1a therapy on conversion to multiple sclerosis in Iranian patients with a first demyelinating event

Abstract: The results of our study, which are consistent with those from western studies, show that treatment at an early stage of MS delays conversion to definite MS and has positive effects on MRI outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The CHAMPS (Controlled High Risk Avonex Multiple Sclerosis Study) trial, 172 which followed up 393 patients for up to 3 years, found a reduction in hazard of more than half (HR 0.49, 95% CI 0.33 to 0.73). The study by Pakdaman et al, 173 which followed up 202 patients for up to 3 years, found a reduction in conversion to CDMS in the IFN-β-1a group (incidence 36.6% vs. 58.2%). We converted this to a HR of 0.54 (95% CI 0.36 to 0.81).…”
Section: Results Of the Assessment Of Clinical Effectivenessmentioning
confidence: 97%
See 3 more Smart Citations
“…The CHAMPS (Controlled High Risk Avonex Multiple Sclerosis Study) trial, 172 which followed up 393 patients for up to 3 years, found a reduction in hazard of more than half (HR 0.49, 95% CI 0.33 to 0.73). The study by Pakdaman et al, 173 which followed up 202 patients for up to 3 years, found a reduction in conversion to CDMS in the IFN-β-1a group (incidence 36.6% vs. 58.2%). We converted this to a HR of 0.54 (95% CI 0.36 to 0.81).…”
Section: Results Of the Assessment Of Clinical Effectivenessmentioning
confidence: 97%
“…[171][172][173][174][175] It should be noted that triallists generally examined time to CDMS, defined using the Poser criteria 64 and involving a second relapse or neurological deterioration, although some also presented analyses examining time to 'McDonald MS', in which MRI findings could be used with clinical findings to arrive at a diagnosis.…”
Section: Results Of the Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…2. The current standard of care of starting treatment early, which makes nowadays treatment-naïve subjects available for clinical trials only when they are at a very early stage of the disease [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: The Adoption Of Mcdonald Criteria That Allowsmentioning
confidence: 99%